Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1248/bpb.30.1468
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Astragalus membranaceus Inhibits the Development of DNFB-Induced Dermatitis in NC/Nga Mice

Abstract: Atopic dermatitis (AD) is one of the most common skin diseases, and is characterized by a chronic and relapsing inflammatory dermatitis with immunological disturbance, e.g., hyper-production of total and specific IgE. Patients with AD usually have a personal or familial history of other atopic diseases.1) Population studies suggest that in most countries AD affects 10-20% of all children at some time during childhood.2) Moreover, AD is a multifactorial disease, and its pathogenesis and etiology are not fully u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…Beside its immunostimulating activity, other studies have shown the direct antimicrobial activity of different extracts and pure compounds that derived from Astragalus species. In mice infected with coxsackie B-3 virus, Astragalus inhibited viral replication in the myocardial tissue while improving abnormal myocardial electric activity (Lee et al, 2007). The antimicrobial and antifungal properties of several crude extracts from different parts of other Astragalus species have been reported (Bisignano et al, 1994;El Sebakhy et al, 1994;Pistelli et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Beside its immunostimulating activity, other studies have shown the direct antimicrobial activity of different extracts and pure compounds that derived from Astragalus species. In mice infected with coxsackie B-3 virus, Astragalus inhibited viral replication in the myocardial tissue while improving abnormal myocardial electric activity (Lee et al, 2007). The antimicrobial and antifungal properties of several crude extracts from different parts of other Astragalus species have been reported (Bisignano et al, 1994;El Sebakhy et al, 1994;Pistelli et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The study duration was 3 weeks, and dermatitis was induced by challenging with 0.15% DNFB twice a week throughout the study period. The D and S groups were treated with distilled and spring water twice a day at room temperature, respectively, and skin symptoms were evaluated as described by Lee et al 14) Briefly, three AD-like symptoms (dryness, crust, keratinization) were scored into four graded severities from 0 (none) to 3 (severe). Total serum IgE was measured using a mouse IgE measurement EIA kit (Yamasa Co., Chiba, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…All mice were coded. To induce atopic dermatitislike skin lesions, a method described by Lee et al (2007) was followed.…”
Section: Methodsmentioning
confidence: 99%